Developing a Framework for Testing Android Applications based on Reverse Engineering Techniques- - Noor Jamal Alkhateeb; Mohammad Saeed AbouTrab (Journal of Digital Information Management, 2019)
It has been recognized that mobile platforms continue to prevail in all aspects of human activity. However, mobile applications might suffer from improper behavior just like other software types. Consequently, there is a growing need for testing mobile applications thoroughly. Model-based testing is one of the popular testing approaches, which depends on having a functional model of system specification to generate and evaluate test cases. In most cases, the specification model is not available, suffers from an unsatisfactory quality, or does not represent all business rules and functional requirements. That would lead to increase in the difficulties in testing, modifying and maintaining mobile applications. Reverse engineering can be used to reveal application’s designs, architecture and knowledge and extract models to represent them.